Optical-conductivity sum rule in cuprates and unconventional charge density waves: a short review - Benfatto, L.; Sharapov, S.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We begin with an overview of the experimental results for the temperature and doping dependences of the optical-conductivity spectral weight in cuprate superconductors across thewhole phase diagram. Then we discuss recent attempts to explain the observed behavior of the spectral weight using reduced and full models with unconventional dx2-y2 charge-density waves.